2017
DOI: 10.3389/fphar.2017.00445
|View full text |Cite
|
Sign up to set email alerts
|

Immune and Metabolic Regulation Mechanism of Dangguiliuhuang Decoction against Insulin Resistance and Hepatic Steatosis

Abstract: Dangguiliuhuang decoction (DGLHD) is a traditional Chinese medicine (TCM) formula, which mainly consists of angelica, radix rehmanniae, radix rehmanniae praeparata, scutellaria baicalensis, coptis chinensis, astragalus membranaceus, and golden cypress, and used for the treatment of diabetes and some autoimmune diseases. In this study, we explored the potential mechanism of DGLHD against insulin resistance and fatty liver in vivo and in vitro. Our data revealed that DGLHD normalized glucose and insulin level, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…DGLHD has been used in clinic as alleviating diabetes, infection, myocarditis, and tuberculosis. Consistently, our previous studies have revealed that DGLHD possesses characteristics of anti-inflammation, immunosuppression, insulin sensitization, hypoglycemia, and hypolipidemia ( Liu et al, 2015 ; Cao et al, 2017 ). In the formula, AG, RR, and RRP are the primary components and exert anti-inflammatory and hepatoprotective effects; GC, CC, and SB act as the ministerial components to strengthen the efficacy of primary agents; AM is the adjunctive component and used to enhance the action or reduce the side effects of primary and ministerial components.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…DGLHD has been used in clinic as alleviating diabetes, infection, myocarditis, and tuberculosis. Consistently, our previous studies have revealed that DGLHD possesses characteristics of anti-inflammation, immunosuppression, insulin sensitization, hypoglycemia, and hypolipidemia ( Liu et al, 2015 ; Cao et al, 2017 ). In the formula, AG, RR, and RRP are the primary components and exert anti-inflammatory and hepatoprotective effects; GC, CC, and SB act as the ministerial components to strengthen the efficacy of primary agents; AM is the adjunctive component and used to enhance the action or reduce the side effects of primary and ministerial components.…”
Section: Introductionsupporting
confidence: 87%
“…Dangguiliuhuang decoction (DGLHD) is a classical TCM formula recorded in “Lan Shi Mi Cang,” which composed of angelica (AG), radix rehmanniae (RR), radix rehmanniae praeparata (RRP), scutellaria baicalensis (SB), coptis chinensis (CC), golden cypress (GC), and astragalus membranaceus (AM) ( Cao et al, 2017 ), and is prepared in line with the China Pharmacopoeia standard of quality control. DGLHD has been used in clinic as alleviating diabetes, infection, myocarditis, and tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it decreased T cells proliferation while increased regulatory T cells (Tregs) differentiation, reduced dendritic cells (DCs) maturation and secretion of IL-12p70 cytokine, decreased DCs-stimulated T cells proliferation, and promoted, the interaction of DCs with Tregs. In adipocytes and hepatocytes as well as DCs and T cells, Dangguiliuhuang Decoction treatment altered PI3K/Akt signaling pathway and increased PPAR-g expression, indicating the ameliorated glucose and lipid metabolism (Cao et al, 2017).…”
Section: Suppress Inflammation and Regulate Lipidmentioning
confidence: 97%
“…), Coptis chinensis Franch., Radix Rehmanniae Praeparata (Rehmannia root), Astragalus propinquus (the root of astragalus membranaceus), Chinese skullcap (Scutellaria baicalensis) and Phellodendron amurense (Phellodendron chinense Schneid. ), is used for the treatment of autoimmune diseases and diabetes (Cao et al, 2017;Cao et al, 2018). In a study of ob/ob mice model, it normalized glucose and insulin level, diminished fat accumulation and lipogenesis, increased the expression of adiponectin, and promoted glucose uptake (Cao et al, 2017).…”
Section: Suppress Inflammation and Regulate Lipidmentioning
confidence: 99%
See 1 more Smart Citation